Corporate Claims Against Director for Paying Bribes on Company’s Behalf: Ho Kang Peng v Scintronix (formerly TTL Holdings) - WAN, Wai Yee (Institutional Knowledge at Singapore Management University, 2014)
Can a company recover the value of the bribe from a director who has paid the bribe, on behalf of the company, to a third party to secure certain benefits for the company, and where it is not alleged that the director had personally benefitted from the bribe? This question raises several complex issues relating to directors’ standard of care, corporate authorisation and corporate illegality, which were considered by the recent decision of the Singapore Court of Appeal in Ho Kang Peng v Scintronix Corp (formerly known as TTL Holdings).